EFFECT OF CHOLECALCIFEROL SUPPLEMENTATION ON HEPATIC STEATOSIS AND GLUCOSE IN OBESE ANIMALS (Arquivos do Mudi, 2023)
Our proposal in this study is that with vitamin D supplementation in obese animals, there willbe reductions in hepatic steatosis and control of blood glucose levels. Male wistar rats wereused (CEUA nº 5866200720). After 21 days of age, they were acclimatized until they were 30days old, from this date on, the obesity induction protocol was initiated, by means of thecafeteria diet. The animals were divided into 2 groups: rats fed a normal diet [control group(CTL n= 24)] another with a hypercaloric diet [obesity induction group (WD n=24)]. After 90days old, they were subdivided into two other groups: CTL-VD (n=12) and WD-VD (n=12)animals in which, were supplemented with vitamin D3 (5.600UI/week, 90 to 130 days old, bygavage). At 131 days old, WD rats exhibited a significantly higher adiposity index than CTLand WD-VD rats. The WD-VD rats had a significantly lower adiposity index than WD rats.The hepatic steatosis was confirmed by biochemical measurements of the total liver lipidcontent increased in WD rats 5% of the liver weight. Vit D3 supplementation decreased BWgain, and reduction of the total lipid total liver in WD-VD rats. The glycemic curve wasperformed and the WD animals showed higher values â€‹â€‹in the first 15 minutes than the CTLanimals. The WD-VD animals presented normal values â€‹â€‹of the area under the curve, in relationto the WD. Vit D supplementation showed that there is a relationship between increasedadipose tissue and circulating vitamin D levels. Supplementation of VD3 attenuated hepaticsteatosis.